(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
Aim of report is to punctuate actuality and benefits can be given by correct management of wood residues at Latvia, in the economic, social, and environmental spheres. Main task is to inform . the public about some outstanding possibilities to utilize wide spectrum of wood residues with certainly positive economic gain, in opposition the state today though residues habitually are damaging the environment with no benefits at all. Especially are given knowledges about ramial chipped wood technology or Sylvasol, and use of wood gasification for asynchronous electro generation needs. Methods used includes studies of literature, analyze o f data available. For the superior effect on peoples lifestyle, economy, life and environment quality as equal of co-solving number of Global environmental problems, introducing the system of wood residues management in Latvia ought to be observed as ultimately profitable fieldfor further outbreaks in environmental sciences and management.